SENSITIVITY OF THE MARINE BENTHIC COPEPOD NITOKRA SP. TO OIL-SUSPENDED PARTICULATE MATTER AGGREGATES (OSA) - Silva, Ana Carina Matos; Guimarães, Sanye Soroldoni; de-Oliveira, Olívia-Maria Cordeiro; Moreira, Icaro Thiago Andrade; Trigüis, Jorge Alberto; Moeira-Cruz, Manoel Jerônimo (Geochimica Brasiliensis, 2018)
In an oil spill in mangrove areas, there is a great possibility of oil aggregation with suspended particulate matter, which may determine the bottom sediment as the final destination of OSA (Oil-Suspended Particulate Matter Aggregates), posing a great risk to Benthic organisms. Ecotoxicity tests with these organisms have been widely used as one of the most accurate forms of biological monitoring of the anthropogenic impacts on this ecosystem. The present work evaluates the ecotoxicity of the exposure to OSA in mangrove sediments, collected along the Pardo river estuary, Canavieiras, Bahia, through pilot scale (microscale) trials. The procedure was performed using acute exposure toxicological tests to determine LC50 (lethal concentration 50%) using the benthic copepod Nitokra sp. For the purpose of comparison, two scenarios were performed, the first considers the aqueous phase of the OSA simulation protocol in microscale, and the second, the elutriate from sediment and oil homogenized in different fractions. It was verified that the formation of the OSA has a much less toxic potential (LC50 70.71) in relation to elutriate formed from the percentages of homogenized sediment with crude oil (LC50 5.59) confirming its potential as an effective form of cleaning for oil treatment in water.